Konjac glucomannan-based nano-fiber membrane delivery system for enhancing anthocyanins stability and regulating oral mucosalpermeation - Sun, Falin; Zhang, Guoqiang; Dong, Qingying; Yang, Baoru; Zhou, Ying; Loyola, Rodrigo Quintana; Ren, Yanzhe Alfonso; Li, Bin; Tian, Jinlong (Elsevier, 2026)
This study develops a core-shell hydrogel nanofiber membrane (NFM) via dynamic rheology-guided spinning and multi-component molecular design to enhance stability and bioactive delivery efficiency. The Konjac glucomannan (KGM)/Polyvinylpyrrolidone (PVP) core forms a 3D gel barrier through hydrogen bonds, inhibiting anthocyanin diffusion (PVP/KGM/ACNs@PVA 6.48 MPa mechanical strength) and enabling 97% release in 120 min. The Polyvinyl alcohol (PVA) shell stabilizes the interface via dynamic hydrogen bonds, achieving 81.22% retention after 8-day light exposure. Cytotoxicity assessment confirmed its good biocompatibility. In addition, NFM can achieve controlled release with a release rate of 97% within 120 min and has a high penetration rate in pig mucosa, with a penetration rate of 53.96% within 5 h. After penetration, it still retains significant antioxidant activity, verifying the feasibility of oral absorption. These findings highlight a rheology-driven strategy for efficient bioactive component delivery.